Predictors of Posterior Glottic Stenosis: A Multi-Institutional Case-Control Study. (March 2016) - Hillel, Alexander T.; Karatayli-Ozgursoy, Selmin; Samad, Idris; Best, Simon R.A.; Pandian, Vinciya; Giraldez, Laureano; Gross, Jennifer; Wootten, Christopher; Gelbard, Alexander; Akst, Lee M.; Johns, Michael M.
Objective: To assess intrinsic and extrinsic risk factors in the development of posterior glottic stenosis (PGS) in intubated patients. Methods: Patients diagnosed with PGS between September 2012 and May 2014 at 3 tertiary care university hospitals were included. Patient demographics, comorbidities, duration of intubation, endotracheal tube (ETT) size, and indication for intubation were recorded. Patients with PGS were compared to control patients represented by patients intubated in intensive care units (ICU). Results: Thirty-six PGS patients were identified. After exclusion, 28 PGS patients (14 male, 14 female) and 112 (65 male, 47 female) controls were studied. Multivariate analysis demonstrated ischemia ( P < .05), diabetes ( P < .01), and length of intubation ( P < .01) were significant risk factors for the development of PGS. Fourteen of 14 (100%) males were intubated with a size 8 or larger ETT compared to 47 of 65 (72.3%) male controls ( P < .05). Posterior glottic stenosis ( P < .01), length of intubation ( P < .001), and obstructive sleep apnea ( P < .05) were significant risk factors for tracheostomy. Conclusion: Duration of intubation, ischemia, diabetes mellitus, and large ETT size (8 or greater) in males were significant risk factors for the development of PGS. Reducing the use of size 8 ETTs and earlier planned tracheostomy in high-risk patients may reduce the incidence of PGS and improve ICU safety.